Actitud y uso de las tecnologías en la información y comunicación en docentes del nivel secundario institución educativa mariscal oscar r. Benavides, distrito de Iquitos 2022 - Pizango Aricara, Elga Raquel (2024)
The objective of this study is to confirm the association between the level of attitudes and the use of ICT among secondary school teachers of the Mariscal Oscar R. Benavides Educational Institute, Iquitos 2022. The research is confirmatory with a descriptive-correlational and transectional design, with a population of 186 secondary school teachers and a sample of 126 subjects, selected through proportional and random distribution, two questionnaires were used. The results showed that the subjects surveyed showed a high attitude towards ICT (53.9%), followed by a medium level (31.0%) and a low level (15.1%). The use of ICT was also mostly high (39.7%) and medium (45.2%) among the teachers surveyed, with a lower percentage at the low level (15.1%). The research demonstrated that there is a relationship between the attitude and the use of ICT in the teachers who are subjects of the study sample, with which the general hypothesis of the research was validated (r=0.621). Specific hypotheses 1, 2 and 3, which indicate that there is a significant relationship between cognitive (r=0.462), behavioral (r=0.623) and behavioral attitudes (r=0.510) with the use of ICT in the teachers who are subjects of the research.